CREDIT DERIVATIVES: TRADING PROTECTION - Valentyn Burianov; Ganna Kulish (Economics & Education, 2024)
The article describes the main forms of credit derivatives, the evolution of their development and conditions of use. Particular attention is paid to the conditions of protection against credit risk. The authors demonstrate the possibility and expediency of using credit derivatives in the financial practice of Ukrainian companies in the context of transformation of the current legislation. It is established that credit notes, as a form of credit derivatives, are a more reliable financial instrument. From an economic point of view, they are considered to be securities with a certain set of risks and benefits for investors, which should be taken into account when developing a financial strategy for all capital market participants. The subject of the study is the intricacies of using credit derivatives in financial management, with a special emphasis on their role and conditions in modern Ukrainian financial practice. The research methodology includes a critical review of the existing literature combined with an analysis of the current use of credit derivatives in Ukraine. This approach offers a dual perspective that not only summarises the global context but also takes into account the nuances of local implementation. The purpose of this study is to investigate the effectiveness of credit derivatives as financial instruments for risk hedging and profitability optimisation. By examining different types of these instruments, the study aims to draw practical conclusions and provide recommendations for integrating these instruments into financial management practices in Ukraine. The research concludes that credit derivatives offer significant advantages as reliable financial instruments that contribute to risk management and economic development. The paper highlights their potential to positively impact financial market development, especially under conditions that facilitate risk hedging. The findings of the publication support the creation of a specific legislative and regulatory framework that would facilitate the wider introduction and efficient use of credit derivatives in Ukraine. This includes emphasising the need for specific amendments to existing tax codes and financial regulations to create a favourable environment for these instruments.